Survival of Curtobacterium flaccumfaciens pv. flaccumfaciens in the soil under Brazilian conditions - Gonçalves, Ricardo M.; Soman, José M. [UNESP]; Krause-Sakate, Renate [UNESP]; Passos, José R. S.; Silva Júnior, Tadeu A. F.; Maringoni, Antonio C. [UNESP] (Springer Nature, 2018)
Common bean has a high relevance for the human diet and a significant socio-economic importance in Brazil. Among the diseases that could infect the crop, bacterial wilt is caused by Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff). Few studies have investigated the survival of this bacteria in the soil; therefore, the objectives of this research were to measure the survival period of several Cff strains as free cells in soil under controlled conditions; the survival period of one strain in types of soils with different chemical and physical compositions as free cells under controlled conditions; and the survival period of one strain as free cells in soil under field conditions. In all measurements, bacterial samples were confirmed as Cff using specific-primers by PCR. We observed a difference in the survival period among Cff strains (varying from 22 to 34 days) and among different soils (varying from 30 to 94 days) under controlled conditions. Under field conditions, the survival period varied from 34 to 80 days as a function of temperature and moisture. These results emphasize the potential Cff survival as free cells in the soil, thereby contributing to the adoption of new management strategies against this disease.
Keywords: Bacterial wilt; Detection; Ecology; Phaseolus vulgaris